1996
DOI: 10.1111/j.1600-065x.1996.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Developmentally Acquired Thymus‐Dependent Tolerance to Central and Peripheral Antigens

Abstract: Current models of tolerance to peripheral, tissue-specific antigens contain some major caveats. First, they consider peripheral tolerance independently from intrathymic T cell selection, a dichotomy that is challenged by observations on TE-induced tolerance. Second, they do not account for the fact that vertebrates are more readily tolerised in development than in adult life. Third, they do not explain the fact that embryonic/neonatal tolerance to foreign tissues can only be induced by HC or TE. A model of thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 59 publications
4
54
0
Order By: Relevance
“…These discrepancies indicate that CD4 ϩ regulatory T cells are heterogeneous, and different experimental systems reveal the predominant effect of regulatory T cells displaying different properties. In spontaneous EAE, our data supports a model in which regulatory T cells display regulatory properties upon leaving the thymus, as has been previously proposed for transplantation tolerance models (52).…”
Section: Discussionsupporting
confidence: 72%
“…These discrepancies indicate that CD4 ϩ regulatory T cells are heterogeneous, and different experimental systems reveal the predominant effect of regulatory T cells displaying different properties. In spontaneous EAE, our data supports a model in which regulatory T cells display regulatory properties upon leaving the thymus, as has been previously proposed for transplantation tolerance models (52).…”
Section: Discussionsupporting
confidence: 72%
“…Several studies using different experimental systems have shown that CD4 ϩ CD8 Ϫ thymocytes can also exert regulatory function (33-37). The intrathymic generation of regulatory T cells (37) supports the idea that these cells are self-reactive (38).…”
Section: Discussionmentioning
confidence: 48%
“…As a corollary, postinjury neuronal survival was improved after the rats were immunized as adults with myelin proteins emulsified in adjuvant or after depletion of regulatory (suppressor) CD4 ϩ CD25 ϩ T cells. Naturally occurring regulatory T cells [apparently the cells that in early studies were identified as thymus-induced suppressor CD4 T cells (17)(18)(19)] may be viewed as safeguards against autoimmune disease. At the same time, as suggested by findings during the past few years (3,5,7) and as shown in the present work, autoimmune T cells are required as safeguards of CNS maintenance in the day-to-day need to cope with stressful conditions.…”
Section: Discussionmentioning
confidence: 99%